The Implications of Food Insecurity at a HBCU (P04-086-19) - Thompson, Linda (Curr Dev Nutr, 2019)
OBJECTIVES: The objectives of the study were: 1) to determine whether there is food insecurity among matriculating students attending a Historically Black College/University (HBCU), 2) to investigate the associations between food security status and the demographic characteristics (gender, classification, housing status) of students, 3) to examine the relationship of food security status to the consumption of fruits and vegetables (FV), 4) to investigate the association of student food security status with overweight/obesity, and 5) to assess fast food consumption among food insecure students. METHODS: Five hundred Seventy undergrad and graduate students were recruited to participate in an online survey. The survey was voluntary and anonymous. Data were collected via a 20-item survey using Qualtrics, an online software program that allows its users to create and distribute survey instruments. The main survey questions were derived the Six-item United States Department of Agriculture-Adult Food Security Survey Module (USDA-AFSSM). The survey also included questions which measured: height and weight, daily fruit and vegetable consumption, fast food purchases and potential food pantry utilization. The remaining questions in the survey determined demographic characteristics which included gender, class, meal plan, and housing status. RESULTS: Data indicated 77.7% (405) of the sample had experienced some level of food insecurity over the last 12 months, whereas 116 (22.2%) were determined to be food secure. The prevalence of the four categories of food security status is shown in Figure 1. Food insecure students were significantly more likely to purchase fast foods two or more times a week and had significantly lower mean fruit and vegetable intakes than food secure students. Sophomores were least likely to be food secure (11.1%), while graduate/professional students were most likely to be food secure (37.6%). Students living on campus were found to be more likely to be food insecure. CONCLUSIONS: The present study provides evidence of significant food insecurity. More fast food and decreased fruit and vegetable consumption was found among the food insecure vs food secure. Food security on college campuses bears further investigation. FUNDING SOURCES: Howard University. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: